The influence of ultrasonic modification on structure of activated carbon and characteristics of supercapacitors on its basis - Ptashnyk, V.V.; Bordun, I.M.; Sadova, M.M. (Functional Materials, 2018)
Influence of ultrasonic radiation during cavitation regime on electrochemical properties of wood based activated carbon was studied. The optimal mode for ultrasonic treatment of activated carbon was determined, wherein the specific capacity of supercapacitors, produced on the basis of such carbon, increases from 52 F/g to 151 F/g. It was shown that ultrasonic treatment does not cause significant changes of the porous structure of the activated carbon but reduces the number of surface groups. The Nyquist plots for supercapacitors made of both original and modified carbon, were analyzed. Equivalent electrical circuits which model the impedance hodograph were constructed. For this purpose, de Levie model was used, modified by parallel RSCCSC - link of chain. It was shown that ultrasonic radiation allows not only to change effectively the properties of a surface, but also shifts a position of the Fermi level to the energy region, which is characterized by a high density of delocalized electron states. Quantity reduction of surface groups and the change of an electronic structure of activated carbon is a reason for the increase of charge accumulation efficiency in an electric double layer at the boundary with electrolyte.